The Role of Psychological and Social Factors on Retail Investor Investment Decisions in the Indonesia Stock Exchange - Fathin, Nadime Abiyyu; Hersugondo, Hersugondo (JDM (Jurnal Dinamika Manajemen), 2022)
Decision-making is a complex process of selecting the best available option from several options. This study examines the psychological and social factors which are affecting investment decisions. Some studies from Western and Middle Eastern countries prove that psychology does have a relationship and influence on investors’ decision-making in their stock market. Based on these, the researchers tried to review the research and add social factors as additional variables. Questionnaires were randomly distributed to 105 investors who are students, private employees, entrepreneurs, civil servants and others from the age range of less than 25 years to more than 55 years who have been involved in the market which shows that psychological factors and social factors as a whole have influence on investment decision making in Indonesia Stock Exchange’s retail investors..